The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2729.2010.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive presence in asynchronous online learning: a comparison of four discussion strategies

Abstract: Some scholars argue that students do not achieve higher level learning, or cognitive presence, in online courses. Online discussion has been proposed to bridge this gap between online and face-to-face learning environments. However, the literature indicates that the conventional approach to online discussion -asking probing questions -does not necessarily advance the discussion through the phases of cognitive presence: triggering events, exploration, integration and resolution, which are crucial for deep knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 35 publications
3
120
0
5
Order By: Relevance
“…Some researchers found that discussion forums promote high quality discussion of course content, allowing students to reflect upon course materials and upon each other's comments (e.g., Walker, 2007). Additionally, the implementation of discussion forums allows students the opportunity to initiate discussions and to drive their own learning (Darabi et al, 2011). In contrast, critiques of the use of discussion forums state that only a small fraction of participants contribute to forums, producing a high quantity of posts in relation to most participants (Coetzee et al, 2014).…”
Section: Student Engagement With Forums In Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers found that discussion forums promote high quality discussion of course content, allowing students to reflect upon course materials and upon each other's comments (e.g., Walker, 2007). Additionally, the implementation of discussion forums allows students the opportunity to initiate discussions and to drive their own learning (Darabi et al, 2011). In contrast, critiques of the use of discussion forums state that only a small fraction of participants contribute to forums, producing a high quantity of posts in relation to most participants (Coetzee et al, 2014).…”
Section: Student Engagement With Forums In Moocsmentioning
confidence: 99%
“…They can be a space for students to interact with other participants, get to know their peers, and learn through their experiences (Young, 2012). They can also be a space for students to check their understanding of the subject matter and to ask questions regarding a task or a problem (Young, 2012;Darabi, Arrastia, Nelson, Cornille, & Liang, 2011). Forums are an environment for cooperation among students (Coetzee et al, 2014) in which students can learn as much from their interactions with others as they do from their interactions with course materials (Thomas, 2002).…”
Section: Student Engagement With Forums In Moocsmentioning
confidence: 99%
“…'the extent to which learners are able to construct and confirm meaning through sustained reflection and discourse in a critical community of inquiry' (Garrison, Anderson, & Archer, 2001, p. 9), can be promoted by engaging learners in critical inquiry, integrating interactions and collaborative tasks in DE courses, and scaffolding discussions by posting meaningful questions and leading the learners to find resolution and reach consensus, as suggested by Darabi, Arrastia, Nelson, Cornille, and Liang (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Forums provide spaces in which everyone's perspective can be stated with equal value (Shank & Cunningham, 1996). In addition to giving a voice to participants, the implementation of discussion forums provides opportunities for participants to initiate discussions and to drive their own learning (Darabi et al, 2011).…”
Section: Participant Engagement With Forums In Moocsmentioning
confidence: 99%
“…Forums can be a space for participants to interact with others, get to know their peers, and learn through their experiences (Young, 2012). They can also be a space for participants to check their understanding of the subject matter and to ask questions regarding a task or an assignment (Young, 2012;Darabi, Arrastia, Nelson, Cornille & Liang, 2011). Forums replace the face-to-face tutorial mode of teaching, allowing a voice for any of the MOOC's participants (Walker, 2007).…”
Section: Participant Engagement With Forums In Moocsmentioning
confidence: 99%